PEMBUATAN PROTOTYPE PLTB TURBIN ANGIN SAVONIUS TIPE-U SUMBU VERTIKAL DENGAN SUDUT KELENGKUNGAN SUDU 135o MENGGUNAKAN SUMBER ANGIN BUANGAN EXHAUST KITCHEN - Wredhira Wirartama, I Wayan Gde; Arta Wijaya, I Wayan; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i04.p32, 2023)
Bali is known as a tourism island for both local and foreign tourists, therefore there are many hotels, resorts and restaurants for tourists. In order to fulfill the Bali Clean and Green program, the Regional Government of Bali encourages tourism-related businesses, such as hotels, to construct sources of electricity from new renewable energy. The authors use waste energy in the form of exhaust wind from the kitchen exhaust fan in addition to using natural wind energy. Artificial wind is created when waste energy from exhaust fans is converted into a form that can be used to rotate or power a generator. Making a PLTB prototype with a vertical axis Savonius turbine with a blade curvature angle of 135 degrees is the goal of this research in order to increase the wind sweep area and obtain the highest output ratio. This study employed a quantitative methodology. This study was able to maximize the exhaust fan's wind speed, which was 5.84 m/s. The highest generator output value is at 2.93 vdc, 0.62 mmA, and 1.80 Watt for a 2-blade turbine and 40 ohm load, and at 3.22 vdc, 0.74 mmA, and 2.39 Watts for a 4-blade turbine and 40 ohm load.